2009
DOI: 10.3904/kjim.2009.24.1.43
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Patient Acceptance and Preferences Between CT Colonography and Conventional Colonoscopy in Colorectal Cancer Screening

Abstract: Background/Aims Colorectal cancer, one of the most common cancers in developed countries, is curable when diagnosed at an early stage. However, for better screening, both a test that patients will tolerate and diagnostic accuracy are required. We compared patient experiences and preferences between computed tomographic (CT) colonography and conventional colonoscopy (CC) under conscious sedation. Methods Patients referred to the gastrointestinal clinic for CC were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 41 publications
4
37
1
Order By: Relevance
“…These authors found that better pain control and optimal quality of information before the ERCP positively influenced patient satisfaction. In a study on the burden of colonoscopy, patients reported a mean score of 1.20 for pain and 1.31 for discomfort on a 7-point Likert scale [15]. Although the results of the aforementioned studies cannot be extrapolated to our results, they confirm our findings that ERCP is burdensome to patients.…”
Section: Discussionsupporting
confidence: 80%
“…These authors found that better pain control and optimal quality of information before the ERCP positively influenced patient satisfaction. In a study on the burden of colonoscopy, patients reported a mean score of 1.20 for pain and 1.31 for discomfort on a 7-point Likert scale [15]. Although the results of the aforementioned studies cannot be extrapolated to our results, they confirm our findings that ERCP is burdensome to patients.…”
Section: Discussionsupporting
confidence: 80%
“…This study showed higher pain and embarrassment scores in the CT-colonography group (n=38 participants) than in the colonoscopy group (n=63 participants) 25. As far as we know, other studies comparing the perceived burden of both techniques used non-randomised tandem designs and were therefore not comparable to our study 7 8 26…”
Section: Discussioncontrasting
confidence: 74%
“…In our study, patients showed better tolerance to CTC and had less discomfort as compared to CC. This has also been shown by studies performed previously (4). CTC is well tolerated in patients aged >60 years in whom colonoscopy is contraindicated or incomplete, despite the presence of sigmoid diverticular disease or colonic redundancy (15,16).…”
Section: Discussionsupporting
confidence: 61%
“…A seven-point Likert scale was used, with the highest score representing the most unfavorable feeling: 7, strongly dislike; 6, dislike; 5, somewhat dislike; 4, undecided; 3, somewhat like; 2, like; 1, strongly like, and the findings were compared (4). Questions about the preferred examination were also asked.…”
Section: Methodsmentioning
confidence: 99%